PERENCANAAN STRATEGIS PEMBANGUNAN KAMPUNG (DESA) - Syahputra Syahputra; Zaili Rusli; Febri Yuliani (Universitas Riau, 2018)
Strategic Planning of Village Development (Village). This study aims to findout the development strategy of Kampung Sabak Auh Siak District. This research usesdescriptive qualitative research method. Primary data is obtained directly from keyinformants, ie stakeholders or layers required by the researcher. Secondary data is obtainedfrom research documents. In this study, the author uses SWOT analysis, namely internalfactors about strength (Strength) and Weakness (weakness) and the results of analysis ofexternal factors of opportunity (opportunity) and treatment (threats). The results of thisstudy indicate some strategic planning that can be carried out, namely human resourcedevelopment, community economy, health services and infrastructure development.